Application of artificial intelligence in predicting lymph node metastasis in breast cancer - Windsor, Gabrielle O.; Bai, Harrison; Lourenco, Ana P.; Jiao, Zhicheng (Frontiers in Radiology, 2023)
Breast cancer is a leading cause of death for women globally. A characteristic of breast cancer includes its ability to metatisize to distant regions of the body, and the disease achieves this through first spreading to the axillary lymph nodes. Traditional diagnosis of axillary lymph node metastasis includes an invasive technique that leads to potential clinical complications for breast cancer patients. The rise of artificial intelligence in the medical imaging field has led to the creation of innovative deep learning models that can predict the metastatic status of axillary lymph nodes noninvasively, which would result in no unnecessary biospies and dissections for patients. In this review, we discuss the success of various deep learning artificial intelligence models across multiple imaging modalities in their performance of predicting axillary lymph node metastasis.